Acetanilide palladacycle: an efficient catalyst for room‐temperature Suzuki–Miyaura cross‐coupling reaction. (30th January 2014) - Dewan, Anindita; Buragohain, Zenith; Mondal, Manoj; Sarmah, Gayatri; Borah, Geetika; Bora, Utpal
<x xml:space="preserve">Abstract</x> The catalytic activity of three acetanilide palladacycles derived from easily accessible and commercially available acetanilide derivatives, viz. N‐phenylacetamide (L1), N‐(4‐chlorophenyl)acetamide (L2) and N‐(4‐methylphenyl)acetamide (L3) has been examined in Pd‐catalyzed Suzuki–Miyaura reaction of arylboronic acid with aryl bromides at room temperature. The complex 1L3 exhibited efficient activity in the Suzuki–Miyaura reaction (up to 99% isolated yield) under mild reaction conditions. Copyright © 2014 John Wiley & Sons, Ltd.